Prescribing patterns of a garment medical centre in Bangladesh - Mohammad Afsan; Muhammad Mahbubul Alam; Nushrat Noor; AH Hamid Ahmed (Update Dental College, 2014)
Objectives: The aim of the study was to audit the prescription and dispensing pattern in a garment medical center to observe the rational use of drug. Irrational use of medicine is a global problem. Polypharmacy, injudicial use of antibiotics, unnecessary use of vitamins are commonly seen in Bangladesh. To find out the current status of the prescribing and dispensing practices and identify factors underlying irrational prescription writing in a Garment medical center for factory workers in Gajipur and to sensitize the future prescribers about the rational prescriptions, this study was carried out. Materials and methods: A cross-sectional descriptive study was carried out to analyze the patterns of prescriptions by using World Health Organization , WHO/INRUD- core drug prescribing indicators and some additional indices. Place and period of study: A total of 300 prescriptions of the patients (garment workers) who had attended in Hannan Textile and Garment Medical Centre, Board Bazar, Dhaka, Bangladesh in between January and November2008 were considered for analysis. Results: The average number of drugs per prescription was 3.1 and no single drug was prescribed by generic name. Use of antibiotic (50% of encounters) was frequent. Only 50.75% drugs were prescribed from national essential drug list (EDL). Percentage of encounters with an antiulcerant, a NSAID and a multivitamin & multimineral prescribed were 41.67%, 46.67% and 23.67% respectively. Conclusion: This study revealed some of irrational practices like poly pharmacy, overuse of antibiotics and vitamins, no use of generic names, and less prescribed from essential drug list. It is suggested that the periodic evaluation of prescribing practices at the healthcare facilities should be done by proper involvement of physician, nurse and pharmacist for the rational use of medicine. DOI: http://dx.doi.org/10.3329/updcj.v3i1.17978 Update Dent. Coll. j: 2013; 3 (1): 07-11